Indoor calibration of Sky Quality Meters: Linearity, spectral responsivity and uncertainty analysis. (September 2016) - Pravettoni, M.; Strepparava, D.; Cereghetti, N.; Klett, S.; Andretta, M.; Steiger, M.
Abstract: The indoor calibration of brightness sensors requires extremely low values of irradiance in the most accurate and reproducible way. In this work the testing equipment of an ISO 17025 accredited laboratory for electrical testing, qualification and type approval of solar photovoltaic modules was modified in order to test the linearity of the instruments from few mW/cm 2 down to fractions of nW/cm 2, corresponding to levels of simulated brightness from 6 to 19 mag/arcsec 2 . Sixteen Sky Quality Meter (SQM) produced by Unihedron, a Canadian manufacturer, were tested, also assessing the impact of the ageing of their protective glasses on the calibration coefficients and the drift of the instruments. The instruments are in operation on measurement points and observatories at different sites and altitudes in Southern Switzerland, within the framework of OASI, the Environmental Observatory of Southern Switzerland. The authors present the results of the calibration campaign: linearity; brightness calibration, with and without protective glasses; transmittance measurement of the glasses; and spectral responsivity of the devices. A detailed uncertainty analysis is also provided, according to the ISO 17025 standard. Abstract : Highlights: Verification of the linear response of Sky Quality Meters from 6 to 19 mag/arcsec 2 based on a novel indoor procedure. Detailed uncertainty calculation. Measurement intercomparison between 16 instruments. Spectral responsivity analysis.